"What I thought was so important isn't really that important": international perspectives on making meaning during the first wave of the COVID-19 pandemic. Issue 1 (1st January 2021) - Todorova, Irina; Albers, Liesemarie; Aronson, Nicole; Baban, Adriana; Benyamini, Yael; Cipolletta, Sabrina; del Rio Carral, Maria; Dimitrova, Elitsa; Dudley, Claire; Guzzardo, Mariana; Hammoud, Razan; Fadil Azim, Darlina Hani; et al.
ABSTRACT: Background: The global COVID-19 pandemic has had a significant impact on the physical and mental health of people everywhere. The aim of the study is to understand how people living in 15 countries around the globe experience an unexpected crisis which threatens their health and that of loved ones, and how they make meaning of this disruption in their narratives. Methods: Data were collected through an anonymous online survey during May–September 2020, which was during or just after the first wave of the COVID-19 pandemic, depending on the country. The questionnaire included demographic and three open-ended questions as prompts for stories about experiences during the initial months of the pandemic. The text was analyzed through inductive thematic content analysis and quantified for full sample description, demographic and subsequently international comparisons. Results: The final qualitative dataset included stories from n = 1685 respondents. The sample was 73.6% women and 26.4% men. The mean age of participants was 39.55 years (SD = 14.71). The identified four groups of overarching themes were: The presence and absence of others; Rediscovering oneself; The meaning of daily life; Rethinking societal and environmental values. We discuss the prevalence of each theme for the sample as a whole and differences by demographic groups. The most prevalent theme referred to disruptions in interpersonal contacts, made meaningful by the increased appreciation of the value of relationships, present in (45.6%) of stories. It was more prevalent in the stories of women compared to men (χ² = 24.88, p  = .001). Conclusions: The paper provides a detailed overview of the methodology, the main themes identified inductively in the stories and differences according to select demographic variables. We identify several major ways of making meaning of the pandemic. The pandemic has impacted many aspects of people's lives which give it meaning, no matter where they live.